Health Psychology : theory, research and practice - Marks, David F.; Murray, Michael; Estacio, Emee Vida. (London : SAGE Publications India Pvt Ltd, 2021)
"A large textbook about health psychology - the sixth edition"--
Keywords: Clinical health psychology -- Health behavior -- Health promotion--Psychological aspects